Risk profiles of suicide attempts among girls with histories of commercial sexual exploitation: A latent class analysis. (March 2023) - Meza, Jocelyn I.; Godoy, Sarah M.; Nguyen, Phuc T.; Perris, Georgia E.; Barnert, Elizabeth S.; Bath, Eraka P.
Abstract: Background: Girls impacted by commercial sexual exploitation (CSE) in the juvenile legal system are three times more likely to have suicide attempts than girls without histories of exploitation. Yet, research on risk profiles and correlates that contribute to elevated suicide risk among girls with CSE histories remains scant. Objective: We sought to examine suicide attempts profiles among CSE-impacted girls in the juvenile legal system. Participants and setting: We partnered with a specialty court for CSE-impacted youth in Los Angeles County. Methods: Data were collected from case files of the 360 girls participating in the court from 2012 to 2016. Latent class analysis was used to identify their profiles of risk indicators. Results: Four risk profiles for suicide attempts emerged: (1) Parental Incarceration (PI; 30 %), (2) Child Welfare Contact (CWC; 25 %), (3) Disruptive Behavior and Sleep Problems (DBS; 25 %), and (4) Pervasive Risk (PR; 22 %). Among youth in the PI group, 5 % had a suicide attempt; however, contrary to our hypothesis, no youth in the CWC group had a suicide attempt. Rates of suicide attempt were significantly higher among youth in the DBS group, as 14 % had a suicide attempt. As hypothesized, youth in the PR were associated with higher risk of suicide attempts, with 28 % reporting a prior suicide attempt. Conclusions: Findings underscore the need for standardized suicide screenings and treatment referrals for girls with CSE histories and suggest an important opportunity for multidisciplinary collaboration with courts to improve suicide prevention strategies. The present study also supports the importance of examining risk across the socioecological context.